(untitled) (Research, Society and Development, 2021)
Oil rents has an impact on the development mechanisms of countries. Considering the relevance of the topic, the objective of this study is to conduct a review of the literature on oil revenue, systematizing the established knowledge and research agendas. The sample used consists of 182 articles collected from Web of Science, in the period from 1978 to August 2020. The results indicate the growth of articles published from 2014, a period coinciding with the fall in oil prices, which impacted countries whose dynamic axis of the economy resides in this sector. Ten countries in terms of authors’ nationality concentrate 58.24% of the authors of the articles on the topic. The article with the highest average citation per year is Regional Favoritism and Khalid Zaman was identified as the main author of the sample. The top scientific journals in terms of quantity of articles and impact factor are Resources Policy and Energy Economics, respectively. The author cocitation network indicated that the leading authors discuss the implications related to natural resource abundance. The co-occurrence network of keywords with the indication of incidence in recent periods, evidenced the direction of studies towards themes related to impacts on growth, the use of empirical methods for studies on the subject, discussion on the abundance, dependence and curse of natural resources, financing of development, the relationship between human capital and oil income, as well as themes related to the environment and sustainability.